The impact of the COVID-19 pandemic on hip and knee arthroplasty: A systematic review - Krisna Yuarno Phatama; I Gusti Ngurah Arga Aldrian Oktafandi; Felix Cendikiawan; Edi Mustamsir (Indonesian Hip and Knee Society (IHKS), 2021)
Background: In order to ameliorate the burden the coronavirus disease 2019 (COVID-19) pandemic had on the medical resources, and to ensure the safety of orthopaedic patients and medical personnel, some hip and knee arthroplasties, as forms of elective surgeries, were suggested to be canceled or postponed. This review aims to analyze the available literature on the impact of COVID-19 pandemic on all areas surrounding hip and knee arthroplasty service. Materials and Methods: A systematic literature search was conducted in five databases from July 5th to 10th, 2020. We included studies that assessed any impacts the COVID-19 pandemic had on the patients who require hip or knee arthroplasty, hip and knee surgeons, and any other areas that are related to hip and knee arthroplasty service. We excluded studies that do not report complete clinical results, reviews, editorials, and letters.Results: After the screening, a total of nine articles were selected. Two studies evaluated the impact of COVID-19 on the hip and knee arthroplasty patients, one study on public interest in hip and knee arthroplasty, three studies on the hip and knee arthroplasty surgeons, two studies on surgical volume, and one study on industry partners. Of 360 surveyed patients, 60% felt anxious about the uncertainty of the rescheduled arthroplasty. Of 1770 surveyed surgeons, 61.9%, 54.7%, and 20.9% of them reported canceled elective inpatient procedures, outpatient procedures, and all types of surgeries, respectively.Conclusions: COVID-19 pandemic had some impacts on the patients, public interest, surgeons, industry partners, and hip and knee arthroplasty volume.